Pattern Recognition : 37th German Conference, GCPR 2015, Aachen, Germany, October 7-10, 2015, proceedings /: 37th German Conference, GCPR 2015, Aachen, Germany, October 7-10, 2015, proceedings. (2015) - Unknown
No abstract available